2019
DOI: 10.26911/thejmch.2019.04.05.01
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analysis on the Determinants of Overweight and Obesity among Primary School Students in Boyolali, Central Java

Abstract: Background:Fat and obesity are serious problems in children because they will continue into adulthood. Diarrhea occurs in groups of children under five years old (toddlers). According to the 2013 risk assessment, in Boyolali District the prevalence of obesity in children was 11.6% consisted of 7.5% fat and 4.1% obese. This study aimed to examine determinants of overweight and obesity among primary school students in Boyolali, Central Java. Subjects and Method: This was an analytic observational study with a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…Adolescents with sufficient physical activity had logodds for obesity 1.12 units lower than those who lacked physical activity (b = -1.12; 95% CI = -2.08 to -0.15; p = 0.023). In line with the study of Wijayanti et al (2019) that physical activity has a negative relationship to obesity in children. Children with high physical activity reduced the risk of high fat and obesity with results (b = -0.04; 95% CI = -0.05 to -0.06; p <0.001).…”
Section: Effect Of Physical Activity On the Risk Of Obesity In High School Adolescentssupporting
confidence: 83%
“…Adolescents with sufficient physical activity had logodds for obesity 1.12 units lower than those who lacked physical activity (b = -1.12; 95% CI = -2.08 to -0.15; p = 0.023). In line with the study of Wijayanti et al (2019) that physical activity has a negative relationship to obesity in children. Children with high physical activity reduced the risk of high fat and obesity with results (b = -0.04; 95% CI = -0.05 to -0.06; p <0.001).…”
Section: Effect Of Physical Activity On the Risk Of Obesity In High School Adolescentssupporting
confidence: 83%
“…Georgina Gómez et al found that SES matches the quality and variety of food [ 26 ]. A multilevel study on childhood determinants of obesity (2019) reported family income and the amount of child allowance was related to obesity and weight gain [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence childhood determinants of obesity (2019) reported family income and the amount of child allowance was related to obesity and weight gain [27]. In many Asian cultures, obesity in children is a sign of their health in affluent families [28], and this belief can explain the prevalence of obesity in families with favourable socioeconomic status.…”
Section: Generalized Obesity Only Abdominal Obesity Only Generalized ...mentioning
confidence: 99%
“…Pocket money also affects over-nutrition because a teenager has many choices to buy snacks or fast food (Wijayanti et al, 2019;Punitha et al, 2014). Low physical activity also affects the nutritional status of adolescents because adolescents generally spend their free time doing light activities without expending a lot of energy, among others, watching movies, television, playing games and social media with gadgets (Cassidy et al, 2017;Chapman et al, 2014) thus leading to overweight and obesity (Wiklund, 2016).…”
Section: Introductionmentioning
confidence: 99%